PERSONALIZED COSMETOLOGY AND ARTIFICIAL INTELLIGENCE - Santos, Stephanye Samara Venicius; Cândido-Santos, Jocsã Hémany; Trancoso, Cauãn Torres; Lira, Ana Amélia Moreira (Seven Editora, 2026)
The convergence of dermatology, biotechnology, and Artificial Intelligence has transformed personalized cosmetology, enabling the development of more precise and targeted formulations based on the integrated analysis of individual data, including skin characteristics, environmental exposures, and genetic predispositions. This chapter addresses the scientific foundations of this approach, its technological applications in the evaluation, development, and recommendation of products, and the economic and market impacts associated with large-scale personalization. The main ethical, regulatory, and methodological challenges related to the treatment of biometric data, the use of genetic testing, and predictive toxicology strategies are also discussed, highlighting future perspectives for safe and sustainable innovation in the cosmetic sector.